Can chronic myeloid leukaemia in children and adolescents be successfully treated without haematopoietic stem cell transplant? A single centre experience. (23rd February 2016) - Giona, Fiorina; Moleti, Maria L.; De Benedittis, Daniela; Santopietro, Michelina; Nanni, Mauro; Testi, Anna M.; Orlando, Sonia; Iori, Anna P.; Piciocchi, Alfonso; Gottardi, Enrico; Barberi, Walter; Diverio, Daniela; et al.
Summary: We analysed the long‐term outcome of 35 children and adolescents (<20 years at diagnosis) with chronic myeloid leukaemia (CML) in chronic phase: 20 patients had received interferon‐alpha and/or tyrosine kinase inhibitors (TKIs), and 15 underwent a haematopoietic stem cell transplant. The 10‐year survival probabilities were similar in transplanted and non‐transplanted patients (73·3% vs. 72·1%, respectively), whereas the survival probability was significantly lower in patients diagnosed before 1999 compared to those diagnosed afterwards (62·1% vs. 100%, P  = 0·0384). The availability of TKIs and the standardized molecular monitoring have significantly improved treatment, management and outcome in children and adolescents with CML.